Exogenous Melatonin Application Prolongs Citrus Fruits (Citrus sinensis) Shelf-life Quality by Enhancing Some Phytochemical Traits - Afsaneh Ansari; Mohammad Saadatian; Ramin Haji-Taghilou; Kadhim Sedeeq; Rawen Abdulhadi; Abdulsameea Majeed (مجله پژوهش‌های علوم و صنایع غذایی ایران, 2025)
This study investigated the impact of melatonin treatments (1 mM and 2 mM) on the post-harvest quality of orange fruit during 30 and 60 days of cold storage. Parameters such as titratable acidity (TA), total soluble solids (TSS), vitamin C, antioxidant capacity, total phenolic compounds (TPC), total flavonoids compounds (TFC), enzymatic activities (PAL, CAT), and color were evaluated. Melatonin significantly improved fruit quality by maintaining higher levels of total soluble solids, vitamin C, and antioxidant capacity. Both treatments effectively reduced weight loss and enhanced the activity of antioxidant enzymes. While 2 mM melatonin showed greater efficacy in the initial stages of storage, 1 mM demonstrated better stability in maintaining quality over extended periods. Melatonin treatments also influenced color parameters, suggesting potential improvements in visual appeal. These findings highlight the potential of melatonin as a natural preservative for enhancing the post-harvest quality and extending the shelf life of orange fruit. Further research is needed to optimize melatonin concentrations and explore its integration with other preservation techniques for sustainable and efficient fruit management.